Social Network Disagreement and Reasoned Candidate Preferences. Issue 1 (January 2020) - Ekstrom, Pierce D.; Smith, Brianna A.; Williams, Allison L.; Kim, Hannah
This study investigates the effects of social network disagreement on candidate preferences. Although much research has explored the effects of disagreement on political tolerance and disengagement, less work has examined the relation between disagreement and political reasoning. We predicted that because disagreement reveals conflicting points of view and motivates people to consider these views, it should promote more effortful reasoning—and thus increased reliance on policy preferences and decreased reliance on party identification when choosing between candidates. Using panel data from the 2008 and 2012 U.S. Presidential elections, we find that respondents in high-disagreement networks tend to shift their candidate preferences to align with their policy preferences regardless of their party identification. In low-disagreement networks, respondents tended to follow party over policy. In sum, the determinants of candidate preferences differ depending on individuals' social networks. In some cases, disagreement may promote more normatively desirable political decision-making.